Pengaruh Variasi Latihan Ladder Drill Terhadap Kelincahan Pemain Ekstrakurikuler Futsal SMA Negeri 6 Malang - Dhoni Arga Hasibuan; Sapto Adi; Nanang Tri Wahyudi; Slamet Raharjo (Universitas Palangka Raya, 2023)
The purpose of this study was to find out how the effect of giving variations of ladder drill exercises on the agility of futsal extracurricular players at Senior High School 6 Malang. Given the characteristics of a fast and dynamic futsal game, a futsal player or athlete needs a good agility component. This study used a pre-experimental method using a one group pretest-posttest design. This research lasted for six weeks with meetings three times a week. There are 10 variations of exercise movements that will be used with the provision that once a week 5 different variations of movements will be selected. The population studied was futsal extracurricular players at Senior High School Negeri 6 Malang with a purposive sampling technique for sampling so that 15 samples were selected according to the research criteria. The instrument used was the Illinois agility test. The data analysis technique used in this study was the paired sample t-test. The results of the t-test show that the analysis of the paired sample t-test of the agility test shows a significance value of 0.000 which is smaller than the 0.05 significance level. This shows that H1 is accepted and H0 is rejected. Therefore, it can be concluded that variations in ladder drill exercises have a significant impact on player agility.